COMPARISON OF OSH REGULATIONS IN INDONESIA WITH STANDARDS INTERNATIONAL (ISO 45001, OSH, ILO) - Yolanda Oktaria (Universitas Teuku Umar, 2026)
Occupational Safety and Health (OHS) is an important aspect in the world of work that has a significant impact on productivity, worker welfare, and company desires. This study aims to analyze and compare the OHS regulations in force in Indonesia with relevant international standards, namely ISO 45001, OHS, and ILO. The research method used is a comprehensive literature study of 20 relevant scientific journals, identified through academic databases and accredited national journals. The journals were evaluated to identify similarities and differences between Indonesian OHS regulations and international standards in terms of requirements, approaches, and levels of protection. The results of the study indicate that there are fundamental similarities in OHS principles, but there are significant differences in the level of detail and specificity of requirements, hazard control approaches, and OHS documentation and reporting.